2018
DOI: 10.3390/met8050315
|View full text |Cite
|
Sign up to set email alerts
|

Research and Development of Powder Brazing Filler Metals for Diamond Tools: A Review

Abstract: Powder brazing filler metals (PBFMs) feature a number of comparative advantages. Among others, these include a low energy consumption, an accurate dosage, a good brazeability, a short production time, and a high production efficiency. These filler metals have been used in the aerospace, automobile, and electric appliances industries. The PBFMs are especially suitable for diamond tools bonding, which involves complex workpiece shapes and requires accurate dosage. The recent research of PBFMs for diamond tools i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Some diamond grits have been broken, and some have been ground during the drilling process because of their different crystal orientations in the drill tool matrix. When compared with that of brazed diamond tools, the good grindability of the solid sintering metal base of these sintered diamond tools is conducive to timely diamond shedding, revealing new cutting edges [17]. The successive breaking of diamond grits on the drill surface helps to maintain the balance between sharpness and service life.…”
Section: Microstructure Of the Segment With 3d Lattice Of Diamond Gritsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some diamond grits have been broken, and some have been ground during the drilling process because of their different crystal orientations in the drill tool matrix. When compared with that of brazed diamond tools, the good grindability of the solid sintering metal base of these sintered diamond tools is conducive to timely diamond shedding, revealing new cutting edges [17]. The successive breaking of diamond grits on the drill surface helps to maintain the balance between sharpness and service life.…”
Section: Microstructure Of the Segment With 3d Lattice Of Diamond Gritsmentioning
confidence: 99%
“…Song et al [16] developed multilayer brazed diamond saw blades through a liquid phase sintering process and found that the sharpness only increased by 22.3%. The disadvantages of the poor self-sharpening ability of multilayer brazed diamond tools are due to their casting microstructure with a poor grindability, which makes it difficult for the diamond grits to protrude from the bonding matrix [17]. Moreover, the diamond grits could be graphitized during the multilayer brazing process, although this can be prevented by treatment with vacuum and argon gas [18].…”
Section: Introductionmentioning
confidence: 99%
“…Today, diamond tools are employed in almost every process of the transformation activity, and therefore, these developments have also led to an increase in research dealing with optimum tool design. For example, there have been studies dedicated to the design of brazed diamond grids: from the earlier work of Sung [ 1 ] to recent review work by Long et al [ 2 ]; models and theoretical analyses of stone sawing with diamonds [ 3 , 4 , 5 , 6 , 7 ], with an emphasis on diamond impregnated segments [ 7 , 8 , 9 ]; industry-oriented evaluation of diamond tools [ 10 , 11 , 12 ], including their long-term performance [ 13 ]; studies on the diamond retention capacity of metal bond matrices [ 14 ]; and optimization of the sintering process of the binding phase and the diamond composite materials [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the brazing diamond technique has been considered to be a promising method of manufacturing diamond tools [1,2]. Owing to the strong chemical and metallurgical bonding within the diamond/filler alloy interface, brazed diamond tools have high bonding strength, grain protrusion and chip storage space [3]; this makes them ideal for the efficient and low-force grinding of difficult-to-cut materials, such as carbides [4], optical glass [5], ceramics [6], aluminium alloy [7], stone [8], and others.…”
Section: Introductionmentioning
confidence: 99%